Ageing, clinical complexity, and exercise therapy: a multidimensional approach - Corrao, Salvatore; Cerasola, Dario; Lucini, Daniela; Argano, Christiano (Frontiers in Sports and Active Living, 2025)
Ageing is a multidimensional concept related to the progressive decline in physiological functions. The decrease of physical autonomy due to the ageing process leads to frailty, which in turn is associated with disability and comorbidity. Ageing represents the primary risk factor for chronic degenerative diseases, especially involving cardiovascular, metabolic, respiratory, and osteoarticular systems, determining the decrease in activities and quality of daily life. Regular physical activity can significantly reduce the risk of chronic degenerative diseases, moderate or severe functional limitations, and premature death in older adults. In light of the relationship between ageing, sedentary lifestyle, disability, comorbidity, and physical activity, a clear need emerges within the health system. Better control on the territory of pathologies related to ageing with the management of clinical and care complexity, multidimensional and multi-professional evaluation of the elderly complex and fragile patient, also through the definition of specific outpatient packages for pathology that allow the simplification of the evaluation process. There is a need for integration between local services, hospitals, and social assistance services. Aim of this review is to highlight the importance of the multidimensional approach is essential to be able to classify the complex elderly patient according to a multi-professional vision aimed at evaluating comorbidities and frailties, including sarcopenia, nutritional deficits, functional capacity, and planning a personalized and monitored motor training program, to improve motor, metabolic, cardiovascular and respiratory functions. In addition, developing an integrated hospital-community-care services management program to follow up with patients post-care is crucial.